2022
DOI: 10.1177/00219983221111492
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing routes of vacuum assisted resin infusion: Numerical investigation

Abstract: The vacuum assisted resin infusion (VARI) process is a cost-effective technique for manufacturing lightweight large complex composite components. It belongs to the liquid composite molding (LCM) family. In this process, a fibrous preform is placed into a mold cavity, and covered by a vacuum bag, then a sealant tape is used to adhere it to the mold in order to avoid air-resin leakage. A vacuum pump is used to evacuate the air from the closed cavity which leads to compact the fabric preform. The inlet gate is op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The polynomial fitting method gave the best fitting result in this study and was therefore selected as the best method to use (as demonstrated by the red solid line in Figure 4). The expression for this method is shown in Equation (8).…”
Section: Parameter Settings 231 Resin Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…The polynomial fitting method gave the best fitting result in this study and was therefore selected as the best method to use (as demonstrated by the red solid line in Figure 4). The expression for this method is shown in Equation (8).…”
Section: Parameter Settings 231 Resin Viscositymentioning
confidence: 99%
“…Vacuum-assisted resin transfer molding (VARTM) utilizes negative pressure from a vacuum to facilitate resin impregnation into fiber fabrics [8]. In comparison to conventional resin transfer molding (RTM), the vacuum properties in the pre-filled region of VARTM enhance the ratio of fiber to resin after impregnation, effectively reducing porosity and increasing the strength of the product after curing [9].…”
Section: Introductionmentioning
confidence: 99%
“…VARIM techniques are applied by stacking the layers on the mold until the desired thickness is reached and after that vacuum is applied to remove air inside the mold cavity. The matrix material (liquid resin) is introduced to the preform via vacuum force and the excess resin is removed from the layers [6]. With this technique, it is possible to fabricate composite materials with minimum resin usage and no air cavities in the material structure that deteriorates the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The deployment of numerical approaches for the prediction of LCM processes has been widely explored in various studies [1,[9][10][11][12][13][14][15][16][17][18][19]. For example, Pierce et al [12] developed a computational model to estimate resin infusion considering the permeability heterogeneities along the preform and tissue deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The Navier-Stokes equations are solved in the region of free flow, whereas the tracking of the flow front of the resin is modeled using the Cahn-Hilliard equation. Ouezgan et al [19] performed a numerical investigation to identify strategies for manufacturing routes that improve parameters such as resin pressure distribution and infusion time. The authors verified that the strategy of resin injection preceding the vacuum step reduced the infusion time in the fibrous medium.…”
Section: Introductionmentioning
confidence: 99%